STUDI KEHILANGAN AIR AKIBAT KEBOCORAN PIPA PADA JALUR DISTRIBUSI PDAM KOTA MAGELANG (STUDI KASUS: PERUMAHAN ARMADA ESTATE DAN DEPKES, KRAMAT UTARA KECAMATAN MAGELANG UTARA ) - Nugraha, Winardi Dwi; K, Dinda Rita (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2010)
Up to the present time, there’re lot of Perusahaan Daerah Air Minum (PDAM) that couldn’t be able toserve their customers in adequate quantity for 24 hours in one day. One of the factor that causing thisproblem are the high lost of water in distribution system that including physic lost and non physic lost.The physic lost is caused due to the pipe leakage in distribution system, so that the quantity of waterthat their use isn’t appropriate to the money that they’re paid. In this research was already been donea study about water losses is caused due to the pipe leakage in Armada Estate and Depkes housingKramat Utara Magelang Utara . On the strength of the first analysis that is done ( WBZ ), water lossesin both of the housing are relative big enough. In north armada estate housing, the water lossesachieves 75,21% and south armada estate housing achieves 43,97%. Whereas in department ofhealth housing, the water losses is lowest than north armada estate and south armada estate. Thewater losses in department of health housing achieves 25,33%.